Pharmacy Student Self-Testing as a Predictor of Examination Performance - Stewart, David (American Journal of Pharmaceutical Education, 2014)
Objectives. To determine if student self-testing improves performance during a doctor of pharmacy course. Methods. Students were given access to online quizzes with a large pool of randomly selected questions specific to upcoming examination content. Quizzes were electronically scored immediately upon completion and students were provided corrective feedback. Results. Examination scores following implementation of the practice quizzes were significantly higher in all but the last testing period. The upper fiftieth percentile of students scored higher on both the practice quizzes and subsequent examinations in all but the fourth testing period. Conclusions. Providing pharmacy students with self-testing opportunities could increase their retention of course material and provide feedback to both students and educators regarding learning, as well as provide students with a measure of their metacognition.